Bibliometric review and analysis: scientific creativity in science education - Suwito Singgih; Nuryunita Dewantari; Suryandari (Institute of Computer Science (IOCS), 2023)
Scientific creativity is one of the higher-order thinking skills that is useful to everyone. Scientific creativity encourages individuals to not only generate creative ideas but also to promote ideas about appropriate technology. This article explains in detail the bibliometric analysis of scientific literature in the field of education from 2017 to 2022. The five-step method was used to conduct the literature review in this study. According to the bibliometric analysis, (1) research on scientific creativity with a high number of citations investigates the relationship between scientific creativity and the ability to think divergently and convergently; (2) There are seven clusters of distribution of scientific creativity research keywords where the variables creativity, assessment, divergent thinking, science, research, cognitive control, stroop assignment, science education, and STEM education seem to be related to scientific creativity; (3) Cognitive control, stroop assignments, research, STEM education, science education, and evaluation are some of the terms that are being used more and more frequently in articles about scientific creativity; and (4) STEM education is a significant phrase in studies that focus on scientific creativity.